2002
DOI: 10.1002/jso.10062
|View full text |Cite
|
Sign up to set email alerts
|

Regression of metastatic carcinoid tumors with octreotide therapy: Two case reports and a review of the literature

Abstract: Background: The antiproliferative effect of the somatostatin analogue, octreotide, on metastatic carcinoid tumors is poorly understood. Partial tumor regression seen radiogaphically has been reported with the use of octreotide therapy for neuroendocrine tumors. Complete regression of carcinoid tumors is rarely reported. Results: Two patients with metastatic midgut carcinoid tumors were treated with subcutaneous octreotide 300 mg/day for symptomatic control of their carcinoid syndrome before debulking palliativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(17 citation statements)
references
References 34 publications
1
16
0
Order By: Relevance
“…[15][16][17] Somatostatin analogues may have antitumour effects 18 and there are occasional reports of dramatic clinical responses. 19 However, tumour regression is modest and a survival benefit has not been definitively proven.…”
mentioning
confidence: 99%
“…[15][16][17] Somatostatin analogues may have antitumour effects 18 and there are occasional reports of dramatic clinical responses. 19 However, tumour regression is modest and a survival benefit has not been definitively proven.…”
mentioning
confidence: 99%
“…Previous studies reported that OCT is an antioxidant that shows protective effects against digestive system tumors and oxidative damage (Leong and Pasieka, 2002). Previously, we also reported that BLM induces severe stress and increases free radical levels, whereas OCT administration significantly reduces this damage.…”
Section: Discussionmentioning
confidence: 92%
“…Leong and Pasieka reported 2 cases of metastatic carcinoid tumors where octreotide was given for symptomatic treatment before the debulking surgery. Previously seen radiographic metastatic lesions were found to be regressed completely on laparotomy [19]. …”
Section: Discussionmentioning
confidence: 99%